KNOWLEDGE AND ATTITUDE TOWARDS CONSUMPTION OF FRUITS AND VEGETABLES AMONG SECONDARY SCHOOL STUDENTS IN IBADAN NORTH EAST LOCAL GOVERNMENT AREA, OYO STATE (2015)
The consumption of fruits and vegetables plays a significant role in human nutrition. Students are more inclined towards taking empty calorie foods with little consideration for healthy foods, especially fruits and vegetables. This has the tendency of pre-disposing them to obesity, dental caries, and other non-communicable diseases in later years. There is a dearth of information on consumption of fruits and vegetables as part of healthy eating among secondary school students. This study was therefore designed to determine the level of knowledge and attitude towards consumption of fruits and vegetables among secondary school students in Ibadan North-East Local Government Area (IBNELGA). This cross-sectional survey involved the use of a four-stage sampling technique in selecting 4 out of 12 wards, 6 schools, 6 classes and 400 students who were selected based on their population from four public schools (369 students) and two private schools (31 students) in IBNELGA. Data were collected using a semi-structured questionnaire and a Focus Group Discussion (FGD) guide. The questionnaire contained 20-point knowledge and 16-point attitude scales on consumption of fruits and vegetables. Knowledge scores of <10 and ≥11 were rated as poor and good respectively, while attitude scores of <8 and ≥9 were classified as negative and positive respectively. Questions were also asked on frequency and reasons adduced for consumption of fruits and vegetables. Six FGD sessions were conducted among the students according to their classes and gender. Quantitative data were analysed using descriptive statistics and Chi-square test at 5% level of significance. Qualitative data were content analysed using the thematic approach. Age of respondents was 14.1±2.0 years. Majority (79.2%) had good knowledge of health benefits of consumption of fruits and vegetables, while 69.8% had positive attitude towards consumption of fruits and vegetables. About 14.0% and 10.0% consumed fruits and vegetables daily respectively. Only 16.2% of the students ate fruits five times or more within the week of the survey, while 9.2% ate vegetables five times or more within that week. Reasons given for consumption of fruits and vegetables by the majority of respondents included taste (78.5%), seasonality (78.2%), knowledge of health benefits (77.5%), knowledge of preparation (72.0%), satisfaction derived from eating (71.0%) and mass media advertisements (67.5%). Students in public schools significantly consumed more fruits everyday than students in private schools.The major perceived reason for consumption of fruits and vegetables was ‘good taste’ but there were negative concerns on certain fruits and vegetables like pear and Vernonia amygdalina (bitter leaf) because of its bitter taste. There was a consensus that education of the students on the health benefits of consumption of fruits and vegetables would increase the intake level. Respondents were knowledgeable and had positive attitude towards consumption of fruits and vegetables while the frequency was low. Thus, secondary school students should be further enlightened on the importance of consumption of fruits and vegetables.